2018
DOI: 10.1051/matecconf/201819702013
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Plasma-activated Medium (PAM) in aqueous solution by an Atmospheric Pressure Plasma Jet (APPJ)

Abstract: Plasma-activated medium (PAM) has been produced by exposing a liquid media to Argon plasma jet. The jet plasma exposure to liquid media has produced reactive Oxygen species (ROS) in liquid phase. This study aims to determine the number of reactive species in plasma-activated medium. An atmospheric pressure plasma jet (APPJ) was generated with a dielectric barrier discharge (DBD) column by AC high voltage. Some parameters varied including exposure time; i.e. 5, 10, 15, 20, 25, and 30 min; and the distance betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Plasma treatment time to activate water also plays a key role in PAW inactivation efficacy. In principle, longer treatment time leads to greater physicochemical changes of PAW, including more acidic pH, higher concentration of reactive species, which have been demonstrated by many studies (Kinandana et al, 2018;Vlad & Anghel, 2017;Zhang et al, 2016Zhang et al, , 2017. Plasma treatment time has been proved to be in a positive correlation with inactivation efficacy (Bakovsky, Fantova, & Chumachenko, 2016;Qi et al, 2018;Zhang et al, 2016).…”
Section: 1mentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma treatment time to activate water also plays a key role in PAW inactivation efficacy. In principle, longer treatment time leads to greater physicochemical changes of PAW, including more acidic pH, higher concentration of reactive species, which have been demonstrated by many studies (Kinandana et al, 2018;Vlad & Anghel, 2017;Zhang et al, 2016Zhang et al, , 2017. Plasma treatment time has been proved to be in a positive correlation with inactivation efficacy (Bakovsky, Fantova, & Chumachenko, 2016;Qi et al, 2018;Zhang et al, 2016).…”
Section: 1mentioning
confidence: 99%
“…(2017) investigated the effect of various distance (from 1 to 4 mm) on the formation of N 2 and OH species close to the water surface, and results showed that the OH concentration was reduced when the gap distance was increased, while the electron density was increased with increased distance, suggesting the particular production of RONS can be tailored via changing the distance. Kinandana, Sumariyah, and Nur (2018) demonstrated that the maximum reactive species (dissolved O 3 and H 2 O 2 ), as well as the most acidic pH were obtained when the distance was 2 cm compared to 1 or 3 cm.…”
Section: Factors Influencing the Inactivation Efficiency Of Pawmentioning
confidence: 99%
“…The important advantages of this system are that it is small and lightweight with a compact design. It is easy to use and can be constructed from cheap, readily available components (Huang et al, 2018;Kinandana et al, 2018;Jung et al, 2022). This research demonstrates the possibility of changing the characteristics of the Al/PVA films by an annealing process to obtain Al 2 O 3 thin films and improve their general performance (Lee, 2013;Baggetto et al, 2015;Parauha et al, 2021).…”
Section: Introductionmentioning
confidence: 75%
“…The value R 1 /R 2 is calculated from the spectra. The electron temperature (Te) can then be calculated using Equations ( 1) and (2) (Kinandana et al, 2018) .…”
Section: Optical Emission Spectramentioning
confidence: 99%
“…Plasma‐facing liquids (PFLs), one type of plasma‐activated liquid, have attracted considerable research attention in terms of the elucidation of its physicochemical properties and the expansion of its application scope. Plasma‐activated liquid refers to all liquid affected by plasma discharge, while PFL has the advantage of being more efficient in that it can supply short‐lived chemical species directly to the liquid surface because the plasma discharge plume faces the liquid surface [22–26] . In particular, when using inert gas such as He as discharge gas, it has the great advantage of being able to keep the temperature of the plasma jet low, so it is particularly strong in the bio‐field where maintaining an appropriate temperature is required.…”
Section: Introductionmentioning
confidence: 99%